Analysis of MICE competition among international conference cities: Using niche theory - Hyojeong Byun (Global Business & Finance Review (GBFR), 2021)
Purpose: The purpose of this study is to understand the competition among international conference cities in South Korea by applying the theory, which is useful for understanding the relationships among individual (industry) groups competing for limited resources. Design/methodology/approach: In this study, data on MICE events (government meeting, corporate meeting, association/group meeting, etc.) held in 2019 in 10 international conference cities including the hosting organizations, event topics, event scales, and conference facilities were completely enumerated, and analyses were attempted. Findings: As a result of the breadth analysis, Changwon (host organization, event topic), Daejeon (event topic, event scale), and Goyang (conference facility) were found to have strong specialized natures. Meanwhile, as a result of the overlap analysis, it was found that Daegu and Gyeongju were in competition with each other according to hosting organizations, Jeju and Gwangju, and Busan and Daejeon according to the scales of events, and Seoul and Daegu, and Changwon and Incheon according to the types of events, Daejeon and Goyang according to event topics, and Changwon and Daegu, and Changwon and Seoul according to conference facilities. Research limitations/implications: Through the findings of this study, implications helpful for the establishment of differentiation strategies for international conference cities were provided. Therefore, although efforts were made to collect data close to complete enumeration, the possibility that there may be missing data cannot be eliminated. Originality/value: This study is meaningful in that presents strategies that help establish differentiation strategies for each International conference cities.
Keywords: 650; Competitiveness; Theory; International Conference City; MICE(Meeting; Incentive; Convention; Exhibition)